O impacto das tarefas de aprendizagem mediadas pela lousa digital interativa na motivação situacional de aprendizes de inglês - Oliveira, Samara Freitas (2014)
Some authors have suggested that learning tasks conducted in L2 classes can motivate learners in different ways. Similarly, Interactive Whiteboards (IWB) have already been linked as drivers to engagement and enthusiasm in L2 classes, which may cause some impact on affective variables that influence learning (e.g. motivation). This crosssectional mixed-methods study aims to understand how situational motivation caused by learning tasks mediated by the IWB impact participants. We seek to answer the following research questions: (1) How does motivation as a personality trait of the learner relate to his/her additional language learning performance?, (2) How does the type of learning task mediated by the IWB impact the learner s motivation?, (3) How does motivation vary along the learning task mediated by the IWB? and (4) What is the relation between the learning task motivation and the learners perception about the task mediated by the IWB? Data collection lasted four months with 29 learners from a private language school. The instruments used were the following: (a) an initial questionnaire (adapted from the Attitudes/Motivation Test Battery by GARDNER, 2004), (b) situation-specific on-line scales to assess learners motivation in three moments: before, during and after the task, and analyze how motivation varies along the task; (c) class observations and field notes resulting from these observations, (d) participants end-of-course grades to understand the connection between academic success and their motivational profiles and (e) a final questionnaire with the qualitative purpose to know learners perceptions about the tasks mediated by the IWB. Our theoretical framework is based on Task-Based Learning and cognitive aspects present in tasks (WILLIS, 1996; SKEHAN, 1996), theories on motivation and second language learning (GARDNER, 2001; DÖRNYEI e OTTÓ, 1998; DÖRNYEI, 2000; 2002) and conceptions about L2 learning mediated by technology (GIBSON, 2001; OLIVEIRA, 2001; MILLER et al, 2005). Our results do not point out to a significative correlation between learners end-of-course grades and their motivational profiles. However, they indicate that there is some variability in situational motivation along the tasks, even among learning tasks from the same type. Furthermore, they show that learners report different perceptions for each learning task and that the impact of the IWB on participants did not have a large proportion